Peculiarities of energy-satiated structure of a small metallic particles formed in a highly unequilibrium conditions; Fizika i Khimiya Obrabotki Materialov; № 4 - Ilyin A. P. Aleksandr Petrovich (1997, 1997)
The physicochemical model of a energy-accumulated metallic particle produced in a highly unequilibrium conditions are examined. It is based on the formation of binary electrical layer in the course of small particles producing. Stability of charge structure (very thin films) is determined by the equilibrium of chemical potentials by electrostatic one. The suggested model allows to explain the energy accumulat that more standard that ion effect melting heat, the stability of electroexplosive ultrafine powders in air, the presence of threshold effects.